Studi Komparatif Implementasi Model Pelayanan Administrasi Kependudukan Berbasis Digital di Indonesia dan Singapura - Ach. Nanang Wijaya; Aminullah Aminullah (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
The digital transformation of population administration services has become a strategic agenda in improving the quality of public services in many countries. This study aims to comparatively analyze the implementation models of digital-based population administration services in Indonesia and Singapore. Using a qualitative approach with a literature review method, this study examines various scientific journals, policy documents, government reports, and relevant publications published in the last five years. The analysis focuses on identifying differences in implementation patterns, supporting and inhibiting factors, and best practices applied in both countries. The results show that Singapore has successfully implemented an integrated and user-centered digital population administration system supported by a strong national digital identity infrastructure, advanced technology, and high digital literacy among citizens. Meanwhile, Indonesia has made significant progress through the implementation of the Population Administration Information System and Digital Population Identity, but still faces challenges such as infrastructure inequality, limited human resource capacity, and uneven digital literacy. This comparative study highlights that the success of digital population administration services is determined not only by technology adoption but also by policy consistency, system integration, institutional capacity, and public participation. The findings are expected to provide policy insights and practical recommendations to strengthen digital population administration services in Indonesia in the future.